Perbandingan akurasi diagnostik antara general practitioner assessment of cognition dan memory impairment screen terhadap mini-cog untuk screening poststroke dementia - Annisa Ismira; Aldy S. Rambe; Fasihah Irfani Fitri (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background : Poststroke dementia is a common type of dementia which diagnosed at least 3 months after stroke. Early detection may relate to a better quality of life of the patients. GPCOG and MIS were proven to be the best instruments to use in screening of postsstroke dementia with high sensitivity and specifity.Objective : The aim of this study was to compare the diagnostic accuracy of General Practitioner Assessment of Cognitions and Memory Impairment Scale to Mini-Cog in screening of poststroke.Method : A cross sectional study of 66 subjects who came to Haji Adam Malik General Hospital with thew history of stroke at least three months before. All the subjects were assessed with Mini-Cog, GPCOG and MIS.Result : Disgnostic analysis of GPCOG in screening of poststroke dementia showed sensitivity 85%; specificity 68^; PPV 74%; NPV 81%; and accuracy 77%. And the diagnostic analiysis of MIS showed sensitivity 97%; speccificity 37%; PPV 62%; NPV 92%; and accuracy 68%.Conclusion : The GPCOG was better in screening poststroke dementia than the MIS with an insignificant difference of accuracy between GPCOG and MIS in screening of poststroke dementia (p=0.94)Keywords : Mini-Cog; GP-COG; MIS; Poststroke Deementia.